Different Enzymatic Processing of γ‐Phosphoramidate and γ‐Phosphoester‐Modified ATP Analogues. (10th January 2017) - Ermert, Susanne; Hacker, Stephan M.; Buntru, Alexander; Scheffner, Martin; Hauck, Christof R.; Marx, Andreas
Abstract: Monitoring the activity of ATP‐consuming enzymes provides the basis for elucidating their modes of action and regulation. Although a number of ATP analogues have been developed for this, their scope is restricted because of the limited acceptance by respective enzymes. In order to clarify which kind of phosphate‐modified ATP analogues are accepted by the α‐β‐phosphoanhydride‐cleaving ubiquitin‐activating enzyme 1 (UBA1) and the β‐γ‐phosphoanhydride‐cleaving focal adhesion kinase (FAK), we tested phosphoramidate‐ and phosphoester‐modified ATP analogues. UBA1 and FAK were able to convert phosphoramidate‐modified ATP analogues, even with a bulky modification like biotin. In contrast, a phosphoester‐modified analogue was poorly accepted. These results demonstrate that minor variations in the design of ATP analogues for monitoring ATP utilization have a significant impact on enzymatic acceptance. Abstract : Enabled cleavage : γ‐Phosphate‐modified ATP analogues with phosphoramidate and phosphoester linkages showed significant differences towards enzymatic cleavage by UBA1 and FAK. Phosphoramidate‐modified ATP analogues were well accepted, whereas the phosphoester‐modified analogue was a poor substrate.